2021
DOI: 10.1002/anie.202111610
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Modulation of A‐Site Vacancies in LaMnO3.15 Perovskite for Surface Lattice Oxygen Activation and Boosted Redox Reactions

Abstract: Modulation of A‐site defects is crucial to the redox reactions on ABO3 perovskites for both clean air application and electrochemical energy storage. Herein we report a scalable one‐pot strategy for in situ regulation of La vacancies (VLa) in LaMnO3.15 by simply introducing urea in the traditional citrate process, and further reveal the fundamental relationship between VLa creation and surface lattice oxygen (Olatt) activation. The underlying mechanism is shortened Mn−O bonds, decreased orbital ordering, promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 53 publications
0
60
0
Order By: Relevance
“…91–93 In addition to investigating the coordination information of noble metals by fitting and analyzing the XAFS data, it has been used to study defects in non-noble metals in recent years. 94 Fig. 5A shows that Co 3 O 4 with different morphologies (rod-, sheet-, and cube-like) exhibited discrepant post-edge oscillation amplitudes.…”
Section: Structural Characterization For Oxygen Vacancies In Catalystsmentioning
confidence: 96%
“…91–93 In addition to investigating the coordination information of noble metals by fitting and analyzing the XAFS data, it has been used to study defects in non-noble metals in recent years. 94 Fig. 5A shows that Co 3 O 4 with different morphologies (rod-, sheet-, and cube-like) exhibited discrepant post-edge oscillation amplitudes.…”
Section: Structural Characterization For Oxygen Vacancies In Catalystsmentioning
confidence: 96%
“…2a, the single peak located between 350 and 650 °C in the O 2 -TPD curve represents the release of the lattice oxygen. 41 Apparently, B–Cu 2 O-1 has the lowest oxygen desorption temperature of 350 °C, while the peak value of O 2 -TPD gradually increases along with the increase in the B-doping content of B–Cu 2 O-2, B–Cu 2 O-3 and B–Cu 2 O-4, respectively. The higher temperature required for the oxygen desorption indicates more stabilized lattice oxygen in the sample.…”
Section: Resultsmentioning
confidence: 92%
“…The optimized models before and after acid etching are shown in Figure S5. With the removal of Co atoms, the adjacent Mn–O bond length was shortened from 1.91 to 1.86 Å (Figure S5), which was conducive to the rapid transfer of the interfacial charge to the reaction site . Bader charge analysis (Table S7) found that the electron cloud density around O atoms decreased after the Co–O bond was broken, which might lead to the weakening of the adjacent Mn–O bond .…”
Section: Resultsmentioning
confidence: 99%